The NAUGHTIEST GIRL Wants To Win - Digby, Anne, 1935-; Hindley, Kate (London : HODDER CHILDREN BOOK, 2021)
Elizabeth is outraged when a new pupil is made head girl instead of her friend Emma. She knows the new girl Kerry isn't as nice as she seems and is determined to prove it. But Kerry is cleverer than Elizabeth thinks. Will she make Elizabeth into the naughtiest girl all over again?
Originally published: 1999.
Based on the characters created by Enid Blyton.
Keywords: Children's stories, English; Adventure and adventurers -- Juvenile fiction